Evaluasi Sistem Informasi Keluarga dalam Aplikasi New Siga di Kabupaten Kotawaringin Timur - Waldianto, Wendy (VISA: Journal of Vision and Ideas, 2025)
This study aims to evaluate the implementation of the New SIGA (Sistem Informasi Keluarga) application in Kotawaringin Timur Regency, focusing on its effectiveness in collecting, processing, and reporting family data. The evaluation framework is based on three key dimensions: input, process, and output. The findings indicate that while human resources and funding are relatively sufficient, the system's optimization is hindered by unequal training opportunities, inadequate facilities, and the absence of local policy support. The process evaluation reveals the lack of measurable annual targets and limited internet access in remote areas, which negatively affect real-time data reporting. Furthermore, monitoring and evaluation are conducted infrequently and without meaningful feedback, leading to suboptimal system performance. Although data reporting reached 95%, it still falls short of complete synchronization with field data. This research highlights the need for systemic improvements in training, infrastructure, and policy integration to enhance the functionality of New SIGA.